Overview and Preparation Guide for Academic Careers in Pediatric Pharmacy, Part 1: Career as a Pediatric Pharmacy Practice Faculty Member - Siu, Anita (J Pediatr Pharmacol Ther, 2019)
Pediatric clinical pharmacy is a growing and evolving field with an increasing number of pediatric clinical pharmacists in academia. In 2017, pediatric practice faculty members represented approximately 7.6% of all pharmacy practice faculty in the United States. The benefits of practicing in an academic environment are many, including, but not limited to, the ability to shape the future of pharmacy practice through the training of the next generation of pharmacists, contributing to science through research and scholarly activities for the care of pediatric patients, and positively impacting patient care for the most vulnerable of patients. Part one of this two-part series describes careers in academic pediatric pharmacy, as well as faculty roles and responsibilities, and provides information and advice related to the preparation and transition into careers in academic pediatric pharmacy.